Measuring Fiscal Policy Uncertainty in Iran - Seyed Hossein Mirjalili; Omid Safari; Ahmad Assadzadeh (Journal of Money and Economy, 2023)
In Iran, following the intensification of economic sanctions during the 2010s and the exacerbation of the government's budget deficit, investment declined starting in 2012, which led to a reduction in GDP. As uncertainty accompanied fiscal policy, its positive effect weakened. We aim to measure fiscal policy uncertainty in Iran using a specified fiscal reaction function tailored to the oil-dependent and sanctions-affected economy in Iran. This function includes two types of shocks: fiscal level shock, and fiscal instability shock, which serves as a proxy for fiscal policy uncertainty. Previous studies used GARCH estimators to measure fiscal policy uncertainty in Iran; however, it cannot separate the instability shock from the level shock. Therefore, we estimated the fiscal reaction function using particle filters for Iran. The results suggest that in 2012, the intensification of sanctions led to an increase in fiscal policy uncertainty in Iran. From 2013 to 2016, the trend of the fiscal policy uncertainty has decreased mildly (by a maximum of 0.04). However, from 2017, the fiscal policy uncertainty index in Iran has rapidly increased, reaching its peak in 2020, whereas Iran's economy had not faced such high fiscal policy uncertainty (a maximum of +0.19) since 1979. In the 2000s, positive growth in fiscal level shocks generally compensated the adverse effects of fiscal policy uncertainty. However, in the 2010s, from 2012 onwards, with the intensification of economic sanctions, fiscal policy uncertainty has dominated over fiscal level shocks. Furthermore, the trend of overall budget balance or deficit closely aligns with the trend of the structural budget balance or deficit in Iran, indicating that the nature of the government's budget is structural and the government's budgetary discretionary decisions have increased during the period of intensified sanctions.
Keywords: 330; Fiscal Policy Uncertainty; Fiscal Shocks; Cyclically Adjusted Budget Balance; Structural Budget